Hasluck Margaret, The Unwritten Law in Albania - Adamus, Jan (Czasopismo Prawno-Historyczne, 1959)
Recenzja: Margaret Hasluck, The Unwritten Law in Albania, edited by J. H. Hutton, Cambridge, at the University Press,1954, s. XV + 285 + 1 mapa.